In vitro evaluation of fungicides against Magnaporthe grisea isolated from rice, finger millet and pearl millet - R.A. SINGH, ARUN KUMAR and (Indian Phytopathology, 2002)
Magnaporthe grisea (Hebert) Barr. (anamorph Pyricularia grisea Sacc.) is one of the most destructive and widespread plant pathogens which parasitizes more than 50 different grass species. Among the cereals, it infects major crops viz., rice, finger millet and pearl millet. Due to extreme variation in the pathogen, resistance in the cultivars does not remain for long. Consequently, fungicides have to be used to manage the disease. It has been observed that the same fungicide is not equally effective against the pathogen on different hosts. Therefore, an attempt was made to compare efficacy of seven fungicides against three isolates of P. grisea isolated from rice, finger millet and pearl millet so that the most effective fungicide could be used against a pathogen host combination.